Eastern Christianity and Late Antique Philosophy - Anagnostou-Laoutides, Evangelia (Texts and Studies in Eastern Christianity Ser, 2020)
Intro -- ‎Contents -- ‎Preface -- ‎Abbreviations -- ‎Notes on Contributors -- ‎Introduction -- ‎Part 1. Identity and Terminology -- ‎Chapter 1. Eastern Christianity and Late Ancient Philosophy: A Conspectus (Parry) -- ‎Chapter 2. Philosophy and Theology in Late Antiquity: Some Reflections on Concepts and Terminologies (Zachhuber) -- ‎Part 2. Greek Christian Thought -- ‎Chapter 3. Drunk on New Wine (Acts 2:13): Drinking Wine from Plato to the Eucharist Tradition of Early Christian Thinkers (Anagnostou-Laoutides) -- ‎Chapter 4. Cyril of Alexandria's Contra Iulianum: Imperial Politics, and Alexandrian Philosophy (c. 416-428) (Crawford) -- ‎Chapter 5. Philosophy as Transformation in Early Christian Thought (Champion) -- ‎Chapter 6. Theology and Philosophy in the Late Patristic Discourse: Pure Existence, Qualified Existence, and the Arbor Porphyriana (Krausmüller) -- ‎Chapter 7. Translating Crisis into Logic: John Damascene's Iconic Conceptualization of History vis-à-vis Late Neoplatonic Symbolism (Adrahtas) -- ‎Part 3. Proclus the Neoplatonist -- ‎Chapter 8. Civic Virtues and the Goal of Likeness to God in Proclus' Republic Commentary (Baltzly) -- ‎Chapter 9. Summarising Platonic Education in Proclus' Reading of Plato's Cave and Divided Line (Miles) -- ‎Part 4. Pagans and Christians in Byzantium -- ‎Chapter 10. Eunapius' Lives of Philosophers and Sophists: Was He Constructing "Pagan Saints" in the Age of Christianity? (Baltussen) -- ‎Chapter 11. A Pagan Philosopher at the Imperial Court: The Case of Pamprepius (McEvoy) -- ‎Chapter 12. Pagan and Christian Dream Theory in Maximus the Confessor (Neil) -- ‎Part 5. Syriac and Arabic Christian Thought -- ‎Chapter 13. The Greek Jargon of Logic and East Syrian Intra-elite Conflicts in the Early Islamic Empire (Kavvadas).